Moving Social Marketing beyond Personal Change to Social Change: Strategically Using Twitter to Mobilize Supporters into Vocal Advocates. Issue 3 (29th August 2014) - Guidry, Jeanine P. D.; Waters, Richard; Saxton, Gregory D.
Abstract : Purpose: This research examines what type of messaging on Twitter is most effective for helping move social marketing beyond focusing on personal changes to find out what messages help turn members of the public into vocal advocates for these organizations' social changes. Design/methodology/approach: Through a content analysis of 3, 415 Twitter updates from 50 nonprofit organizations, this study identifies specific types of messages that are more likely to get stakeholders retweeting, archiving, and discussing the organizations' messaging through regression analysis. Findings: Messages focusing on calls-to-action and community building generated the most retweets and Twitter conversation; however, they were also the least used strategies by nonprofit organizations. Originality/value: Research has regularly examined the types of messages sent out by nonprofit organizations on Twitter, but they have not tested those messages against measures of engagement. This study pushes the understanding of social media communication to the next level by analyzing those message categories against metrics provided by Twitter for each tweet in the sample.